Motion characteristics and aero-elastic responses of floating offshore wind turbine under coupling action of waves and winds - Wang, Bin; Li, Ying; Gao, Shan; Shen, Kanmin; Hu, Zhenhong; Zheng, Xing (Frontiers in Environmental Science, 2022)
As a complex multi degree of freedom coupling system, floating offshore wind turbine usually works in complex and changeable marine environment. The research of floating offshore wind turbine often needs to consider the coupling effect of wind, wave and current at the same time. Under the action of wind and wave load, floating offshore wind turbine will produce a large motion response. Generally, the surge motion and pitch motion are the most obvious aspects, and their motion amplitude is also the largest, and large-scale motion of the floating platform will directly affect the relative velocity of the wind loaded flow. Therefore, the surge motion and pitch motion usually have the most obvious impact on the aerodynamic load of wind turbine. In this paper, the motion characteristics and aeroelastic responses of the DTU-10MW semi-floating offshore wind turbine under coupling action of wind and wave are simulated. The motion characteristics and aeroelastic responses of floating offshore wind turbine are calculated under different wind and wave combination conditions, and the influence law of wind and wave action are summarized. The results show that wind load affects the mean value of motion of the floating offshore wind turbine, and wave load affects the amplitude of motion; Finally, the dynamic response of the wind turbine with the included angle of the wind and wave load is discussed and analyzed, and the influence of the incident angle of the wind wave on the motion response of the floating offshore wind turbine is analyzed.